2020
DOI: 10.26858/jptp.v6i1.11275
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitas Air pada Kawasan Budidaya Rumput Laut Eucheuma Cottoni di Kabupaten Jeneponto

Abstract: Penelitian ini bertujuan untuk mengetahui Kualitas Air pada Kawasan Budidaya Rumput Laut Eucheuma cottoni di Kabupaten Jeneponto yang terkait dengan parameter fisika, kimia dan biologi. Penelitian ini merupakan jenis penelitian deskriptif dengan menggunakan metode survei, penelitian ini dilakukan dengan mengambil sampel air pada dua stasiun berbeda yakni, Desa Tanrusampe dan Desa Bontosunggu, Kabupaten Jeneponto pada musim hujan. Hasil penelitian ini menunjukkan bahwa kualitas air stasiun 1 (Desa Tanrusampe) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 3 publications
0
13
0
12
Order By: Relevance
“…The same finding was also reported by Ya'la & Nasmia (2012) that good seaweed cultivation area should be able to have good water brightness. According to Atmanisa (2020), the brightness level for algae cultivation is greater than 5 meters. Turbid waters have many fine particles floating in the water and attached to the thallus can inhibit the absorption of food and the photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The same finding was also reported by Ya'la & Nasmia (2012) that good seaweed cultivation area should be able to have good water brightness. According to Atmanisa (2020), the brightness level for algae cultivation is greater than 5 meters. Turbid waters have many fine particles floating in the water and attached to the thallus can inhibit the absorption of food and the photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…According to SNI 7673.2.2011 (BSN 2011), the water quality standard for the longline method of Eucheuma cottoni seaweed cultivation is 28-33 ppt. According to Atmanisa et al (2020), Eucheuma cottoni is one of the stenohaline seaweeds, high salinity fluctuations can affect the seaweed osmoregulation process. The results showed that the salinity in Ekas Bay exceeds the SNI standard, so that it can cause seaweed to be susceptible to disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on field data, it shows that the brightness conditions in the sea waters at the study site are > 1 meter. This condition shows the suitability for seaweed growth, and can be used for grouper and snapper cultivation but is not good for pearl oyster growth which requires relatively higher brightness (>3.5 m) [14]. DO measurement results from all stations indicate a range that meets the requirements for living and growing marine biota.…”
Section: Sea Water Chemistrymentioning
confidence: 93%